Biomass-derived porous carbon anode for high-performance capacitive deionization. (10th November 2018) - Xie, Zhengzheng; Shang, Xiaohong; Yan, Junbin; Hussain, Taimoor; Nie, Pengfei; Liu, Jianyun
Abstract: The carbon material derived from citrus peel was prepared via hydrothermal synthesis method with low amount of ZnCl2 . The morphology and surface structure of the synthesized carbons were characterized by field emission scanning electron microscope (FESEM), X-ray diffraction (XRD) and N2 adsorption/desorption isotherms measurements. The electrochemical and capacitive deionization performance of carbon materials were comparatively studied by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and galvanostatic charge-discharge (GCD). Compared with the materials activated with KOH or H3 PO4, ZnCl2 -activated carbon showed the best electrochemical double-layer characteristics, with the specific capacity of 120 F g −1 . When being applied as anode in the capacitive deionization (CDI) cell, the desalination amount of 16 mg g −1 and the average salt adsorption rate ( ASAR ) of 0.67 mg g −1 min −1 were achieved, which is much higher than those of KOH- and H3 PO4 -activated materials. The desalination amount retained 80% after 35 cycles. The possible mechanism is proposed in light of X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) analysis. This work provides a facile and environmentally friendly method for the preparation of a green and low cost biomass derived porous carbon material by fruit waste with a low amount (1% mass) of activation regents for high performance capacitive deionization. Graphical abstract: Highlights: The porous carbon derived from fruit waste was prepared via hydrothermal synthesis method. The carbon activated with low amount (1% mass) of ZnCl2 showed the best porous characteristics. The ZnCl2 -activated carbon exhibited the best electrochemical and desalination performance. The +C-Zn||AC cell shows high desalination rate and excellent desalination and regeneration stability.